Rancang Purwarupa Aplikasi Becakap Bagi Masyarakat Pesisir dengan Pendekatan Design Thinking - Steffi Adam; Suryo Widiantoro (Journal of Applied Informatics and Computing, 2019)
The purpose of this study is to design an application prototype that can help the distribution of information for coastal communities. The Riau Islands Province Medium Term Regional Development Plan 2016-2021 explains that investment opportunities in the Riau Islands begin to penetrate the coastal areas. The Batam City Government is try to ensure equitable development through access to information technology, but coastal communities still have difficulty utilizing the information technology. This research is a qualitative research with a Design Thinking approach. The Design Thinking approach has five stages namely emphatize, define, ideate, prototype, test, and implement. Design Thinking Approach is an approach used to create innovation by focusing on "Human Centered Design". Data collection methods that will be used in this study are observation and interviews. The results of this study are the Becakap Prototype application which has four functions, namely scholarship information, sea level information, weather information, and for action. This application makes it easy for coastal communities to access the information needed.